DATING NORMS IN THE SOCIETY OF KAZAKHSTAN - Absattar, Alua (Nazarbayev University School of Sciences and Humanities, 2024)
This study explores the interaction between these norms and dating patterns among young adults in Kazakhstan. It is done through qualitative methods to demonstrate the ways in which traditional and modern gender norms impact dating gender norms, behaviors and experiences, offering perspectives on the changing landscape of Kazakhstani dating culture, the research demonstrates the complex interactions associated with changing traditional practices coexisting with increasing modern gender norms. Through an analysis of these delicate interactions, the research improves our awareness of gender roles and the dynamics of dating in a society that is transforming.
Keywords: Type of access: Open Access; dating norms; Kazakhstan; young adults; dating practices; gender norms; cultural traditions; modern influences; societal change